The Effect of Company Size, Tax Haven, and Foreign Ownership on Thin Capitalization Practices with ROA as a Control Variable - Faza, Cikal Aqilah; Taqi, Muhamad; Mukhtar (SMART Insight, 2024)
The practice of thin capitalization is a form of international tax avoidance. The trick is to hoard debt to be calculated as a tax-deductible expense. This design arises because tax provisions distinguish the treatment between interest and dividends. This research examines how the size of a company, tax haven, and foreign ownership affect thin capitalization and uses Return on Asset (ROA) as a control variable. Listed on the IDX are companies from the manufacturing sector for the years 2018 to 2022, which comprise the population for this study. The research sample selection used the purposive sampling method and obtained a sample of 275 samples that met the criteria and data processing using the SPSS 25 application. This study shows the results: company size has a positive effect on thin capitalization, tax haven has a negative effect on thin capitalization, foreign ownership has no effect on thin capitalization and ROA as a control variable has no effect on thin capitalization.